EFEKTIFITAS PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DALAM MENGOPTIMALKAN KINERJA MANAJERIAL PADA PERUSAHAAN DAERAH PAJAK HORAS JAYA (PDPHJ) PEMATANGSIANTAR - Harahap, Indah Dwi Pramita; Simbolon, Deli Yanti; Gultom, Jenni; Silitonga, Hery Pandapotan (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Responsibility accounting is a system designed to collect and report costs according to the responsibility center in achieving organizational goals. This study aims to determine the effectiveness of the application of accountability accounting in optimizing managerial performance. This research was conducted at the Regional Pajak Horas Jayai Pematangsiantar. Sources of data using primary and secondary data. Data collection techniques by observation, documentation, and interviews. The data analysis technique used qualitative analysis. The results of research on the application of high responsibility accounting, it will improve managerial performance. Responsibility centers in organizations that have managers will control and be responsible for costs, profits and investments, this will increase morale because they believe that they are working for a common goal.